A 5′-Phosphodiester Group Attached to Deoxyguanosine does not Accelerate the Hydrolysis of cis-[PtCl(NH3)2(dGuo)]+. Issue 1 (1999) - Weber Weber, Tiphaine Tiphaine; Legendre Legendre, Franck Franck; Novozamsky Novozamsky, Veronika Veronika; Kozelka Kozelka, Jiří Jiří
Abstract : The influence of the methylphosphoester group on the reversible reaction shown below was studied. Evaluation of the rate constants for the system depicted as well as for the analogous equilibrium involving the nucleoside deoxyguanosine showed that whereas the chloride anation is slowed down by the presence of the methylphosphoester group, the hydrolysis rate constant is not significantly altered. This result speaks against a catalytic role of the 5'-phosphodiester group in the hydrolysis of cisplatin monoadducts with DNA, as suggested previously (Kozelka & Barre, Chem. Eur. J. 1997, 3, 1405-1409).